PENINGKATAN ENTREPRENEUR SKILL SISWA SMA MELALUI PELATIHAN PENCIPTAAN IDE BISNIS - Mustafida, Nurul; Suminto, Miftahul Adi; Herlina, Erida; Sari, Linda Purnama; Puspitaningrum, Ari Cahaya; Nisa, Faizatun; Firmansyah, Muhammad Rafli (Universitas Mataram, 2025)
A Community Service program in the form of business idea creation training was implemented at SMA Negeri 8 Surabaya as an effort to strengthen students' entrepreneurial skills and equip them with practical knowledge for life after graduation. The primary objective of this activity was to enhance students’ understanding of entrepreneurship and to foster the development of applicable business ideas through the Business Model Canvas (BMC) approach. The training was conducted using a structured method that included interactive lectures, group discussions. BMC development, and evaluation of comprehension through pre-test and post-test assessments. A total of 210 twelfth-grade students participated in the program and were divided into groups to design business plans based on the BMC framework. The results demonstrated an overall increase in entrepreneurial knowledge, business activities, and understanding of fundamental BMC concepts, with more than 80% of students showing improved post-test scores compared to pre-test results. These findings indicate that the training was effective in enhancing both theoretical knowledge and practical entrepreneurial skills, despite several limitations related to facilities, time management, and the large number of participants. It is therefore recommended that similar activities be continuously implemented with the support of schools and external partners to ensure the sustainability and further development of students' business ideas toward real-world application.